Multimodality management of cavernous sinus meningiomas with less extensive surgery followed by subsequent irradiation: Implications for an improved toxicity profile - Omer Sager; Murat Beyzadeoglu; Ferrat Dincoglan; Selcuk Demiral; Hakan Gamsiz; Bora Uysal; Onurhan Colak; Fatih Ozcan; Bahar Dirican (Journal of Surgery and Surgical Research - Peertechz Publications, 2020)
Meningiomas comprise the most frequent intracranial benign tumors accounting for approximately one third of all intracranial neoplasms, and generally follow an indolent disease course with a typically benign nature and slow-growing behaviour. Although majority of meningiomas may follow an indolent disease course, affected patients may suffer from a plethora of symptoms with regard to lesion location. Symptoms typically occur as a result of the mass effect leading to compression of critical neurovascular structures. Headache, focal seizures, weakness in the limbs, visual disturbances, loss of smell, impaired memory or hearing functions may be observed. Advances in neurosurgery may allow for an improved toxicity profile following surgical resection as the traditional and a leading mode of management for meningiomas located at accessible brain areas. Nevertheless, vigilance is required given the morbidity and mortality risks associated with meningioma surgery particularly for elderly patients. In this context, radiation therapy (RT) may offer a viable alternative or adjunctive modality of management for meningiomas. Management of cavernous sinus meningiomas in intricate association with critical neurovascular structures pose a formidable challenge to the treating physicians. Attempting at extensive surgical procedures may be associated with substantial morbidity and even mortality. In this context, selected patients may benefit from a tailored multimodality approach including less extensive surgical resection followed by subsequent irradiation. Primary advantages of this refined therapeutic strategy may include improved toxicity profile along with improved functionality and quality of life. Herein, we assess multimodality management of cavernous sinus meningiomas with less extensive surgery followed by subsequent irradiation.